Advanced progress of the relationship between PCSK9 monoclonal antibodies and hyperglycemic adverse events - Zhang, Ruixing; Wang, Yongxiang; Peng, Yu; Zhao, Jing; Zhang, Zheng (Frontiers in Cardiovascular Medicine, 2023)
Purpose of Review Long-term use of statins had been confirmed to cause an increase in hyperglycemic adverse events (HAEs), whose mechanism has been well understood. Proprotein convertase subtilisin/kexin type 9 (PCSK9) monoclonal antibodies (PCSK9-mAbs), a kind of new lipid-lowering drug, can effectively reduce plasma low-density lipoprotein cholesterol levels in patients with CHD and have been widely used. However, animal experiments, Mendelian randomization studies, clinical researches and Meta-analyses which focused on the relationship between PCSK9-mAbs and HAEs had reached different conclusions, which has attracted great attention from clinicians. Recent Findings The newest FOURIER-OLE randomized controlled trial followed PCSK9-mAbs users for over 8 years, whose results suggested that long-term use of PCSK9-mAbs did not increase the incidence of HAEs. Newest Meta-analyses also indicated that there was no relationship between PCSK9-mAbs and NOD. Meanwhile, genetic polymorphisms and variants related to PCSK9 might have effects on HAEs. Conclusion According to the results of current studies, there is no significant relationship between PCSK9-mAbs and HAEs. However, longer-term follow-up studies are still needed to confirm it. Although PCSK9 genetic polymorphisms and variants may affect the possible occurrence of HAEs, there is no need to perform relevant genetic testing before applying PCSK9-mAbs.